2005
DOI: 10.4192/1577-8517-v5_5
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence Concerning Smes Corporate Websites: Explaining Factors, Strategies and Reporting

Abstract: Abstract. The important role played by Small and Medium-sized Enterprises in any contemporary economy as a motive force for generating employment and wealth is universally acknowledged and therefore this work is based upon a more detailed study concerning the efficiency of SMEs.Therefore by analysing a sample of 816 SMEs, we aim to study the information published on their Websites in order to clarify certain doubts with respect to the type of target users and thus discover the objectives and strategies pursued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
3
22
0
1
Order By: Relevance
“…Empirical findings suggest a significant relationship between the firm size and online disclosure (Hossain et al, 1995;Ashbaugh et al, 1999;Craven and Marston, 1999;Pirchegger and Wagenhofer, 1999;Brennan and Hourigan, 1998;Bonson and Escobar, 2002;Debreceny et al, 2002;Ettredge et al, 2002;Larrán and Giner, 2002;Oyelere et al, 2003;Marston and Polei, 2004;Xiao et al, 2004;García-Borbolla et al, 2005;Bollen et al, 2006;Ezat and El-Masry, 2008). This prompts the second research hypothesis:…”
Section: Firm Sizementioning
confidence: 99%
“…Empirical findings suggest a significant relationship between the firm size and online disclosure (Hossain et al, 1995;Ashbaugh et al, 1999;Craven and Marston, 1999;Pirchegger and Wagenhofer, 1999;Brennan and Hourigan, 1998;Bonson and Escobar, 2002;Debreceny et al, 2002;Ettredge et al, 2002;Larrán and Giner, 2002;Oyelere et al, 2003;Marston and Polei, 2004;Xiao et al, 2004;García-Borbolla et al, 2005;Bollen et al, 2006;Ezat and El-Masry, 2008). This prompts the second research hypothesis:…”
Section: Firm Sizementioning
confidence: 99%
“…When a website has comprehensive, focused information, users are more likely to make better-informed decisions and, thus, information content is an important antecedent of customer satisfaction and purchase intention (Thongpapanl and Ashraf, 2011). It comes as no surprise, then, that former website evaluation studies have analysed in detail this dimension on SME (Burgess et al, 2009;García-Borbolla et al, 2005;Mendo and Fitzgerald, 2005;Meroño-Cerdan and Soto-Acosta, 2007;Schmidt et al, 2008;Sun et al 2012), although not always using the same website features in a consistent way. Given that it incorporates distinct types of information, the informative dimension can be divided into two separate dimensionsorganisation information and commercial information.…”
Section: Website Content and Designmentioning
confidence: 99%
“…Empirical work has found that the presence of contact details, social networking and other communication features in websites positively influence trust and purchase intention (Lee and Kozar, 2012). Reflecting perhaps the value of this dimension, previous studies have analysed several communication features on SME websites, specifically those related with the enterprise contacts and with conventional forms of communication (García-Borbolla et al, 2005;Soto-Acosta and Meroño-Cerdan, 2006;Sun et al, 2012). Web 2.0 communication features are only now starting to receive attention from investigators (Kim et al, 2011).…”
Section: Website Content and Designmentioning
confidence: 99%
See 2 more Smart Citations